PARAMETER ESTIMATION AND ANALYSIS OF AVERAGE YEARS OF SCHOOLING IN MERAUKE DISTRICT WITH BIRNBAUM-SAUNDERS DISTRIBUTION APPROACH - Agustinus Langowuyo; Sara Yokhu; Felix Reba (Department of Mathematics, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2025)
Average years of schooling is an important indicator in assessing the success of education development in a region. This study aims to analyze data on average years of schooling in Merauke Regency, Papua Province, using the Birnbaum-Saunders (BS) Distribution approach. This distribution was chosen because of its ability to model data that has asymmetric characteristics and low variability. The parameters resulting from the analysis include a scale parameter (Î²) of 8.35, which reflects the average years of schooling of the population, and a shape parameter (Î±) of 0.0545, which indicates the low degree of dispersion of the data around the mean. The results of the analysis show that the average length of schooling in Kabupaten Merauke is at the junior high school (SMP) level, with a homogeneous data distribution. This homogeneity reflects good equity in access to education, but also indicates the potential for stagnation at certain levels of education. The Birnbaum-Saunders distribution proved to be effective in modeling education data in this region, providing a more accurate picture than traditional approaches. This research makes an important contribution in understanding the distribution pattern of average years of schooling in Merauke district. The results can be used as a basis for designing more targeted policies in improving the quality and access to education, especially at the senior secondary level. In addition, this approach can serve as a reference for analyzing education in other regions with similar geographical and socio-economic challenges